An improved space domain algorithm for determining the 3-D structure of the magnetic basement - Hang, Nguyen Thi Thu; Oksum, Erdinc; Minh, Le Huy; Thanh, Do Duc (Vietnam Journal of Earth Sciences, 2019)
The paper presents an improved algorithm based on Bhaskara Rao and Ramesh Babu’s algorithm to invert magnetic anomalies of three-dimensional basement structures. The magnetic basement is approximated by an ensemble of juxtaposed vertical prisms whose bottom surface coincides with Curie surface with the known depth. The computer program operating with the proposed algorithm is built in Matlab environment. Test applications show that the proposed method can perform computations with fast and stable convergence rate where the results also coincide well with the actual model structure. The effectiveness of the method is demonstrated by inverting magnetic anomalies of the southeast part of Vietnam continental shelf. The calculated magnetic basement relief of the study area provides useful additional information for studies in the aim of dealing with the geological structure of the area. References Beiki M., 2010. Analytic signals of gravity gradient tensor and their application to estimate source location, Geophysics, 75(6), i59–i74. Bui C.Q. (chief author), Le T., Tran T. D., Nguyen T. H., Phi T.T., 2007. Map of deep structure of the Earth’s crust, Atlas of the characteristics of natural conditions and environment in Vietnam’s waters and adjacent region. Publisher of Science and Technology, Ha Noi. Do D.T., Nguyen T.T.H., 2011. Atempt the improvement of inversion of magnetic anomalies of two dimensional polygonal cross sections to determine the depth of magnetic basement in some data profile of middle off shelf of Vietnam. Journal of Science and Technology, Vietnam Academy of Science and Technology, 49(2), 125–132. Do D.T., 2013. Study for application of 3D magnetic and gravity method to determine density contribution of basement rock and depth of magnetic basement on Vietnam’s shelf for oil research and prospecting Vietnam National University, Hanoi, Project code QG-11-04. Keating P. and Pilkington M., 2000, Euler deconvolution of the analytic signal, 62nd Annual International Meeting, EAGE, Session P0193. Keating P., Zerbo L., 1996. An improved technique for reduction to the pole at low latitudes, Geophysics, 61, 131–137. Le H.M., Luu V.H., 2003. Preliminary interpretation of the magnetic anomalies of the Eastern Vietnam sea and adiacent regions. J. Sci. of the Earth, 25(2), 173–181. Mai T.T., Pham V.T., Dang V.B., Le D.B., Nguyen B., Le V.D., 2011. Characteristics of Pliocene - Quaternary geology and Geoengineering in the Center and Southeast parts of Continental Shelf of Vietnam. J. Sci. of the Earth, 33(2), 109-118. Mushayandebvu M.F., Lesur V., Reid A.B., Fairhead J.D., 2004. Grid Euler deconvolution with constraints for 2D structures, Geophysics, 69, 489–496. Nguyen N.T., Bui V.N., Nguyen T.T.H., Than D.L., 2014a. Application of power density spectrum of magnetic anomaly to estimate the structure of magnetic layer of the earth crust in the Bac Bo gulf. Journal of Marine Science and Technology, 14(4A), 137–148. Nguyen N.T., Bui V.N., Nguyen T.T.H., 2014b. Determining the depth to the magnetic basementand fault systems in Tu Chinh - Vung May area by magnetic data interpretation. Journal of Marine Science and Technology, 14(4A), 16–25. Nguyen T.T.H., Pham T.L., Do D.T., Le H.M., 2018. Improving algorithm of determining the coordinates of the vertices of the polygon to invert magnetic anomalies of two-dimensional basement structures in space domain, Journal of Marine Science and Technology (preparing to print). Parker R.L., 1973. The rapid calculation of potential anomalies, Geophys. J. Roy. Astron. Soc, 31, 447–455. Pilkington M., Gregotski M.E., Todoeschuck J.P., 1994. Using fractal crustal magnetization models in magnetic interpretation, Geophysical Prospecting, 42, 677–692. Pilkington M., 2006. Joint inversion of gravity and magnetic data for two-layer models, Geophysics, 71, L35–L42. Rao D.B., Babu N.R., 1993. A fortran 77 computer program for three dimensional inversion of magnetic anomalies resulting from multiple prismatic bodies, Computer & Geosciences, 19(8), 781–801. Tanaka A., Okubo Y., Matsubayashi O., 1999. Curie point depth based on spectrum analysis of the magnetic anomaly data in East and Southeast Asia, Tectonic Pphysics, 306, 461–470. Thompson D.T., 1982. EULDTH – A new technique for marking computer-assisted depth estimates from magnetic data, Geophysics, 47, 31–37. Vo T.S., Le H.M., Luu V.H., 2005. Determining the horizontal position and depth of the density discontinuties in Red River Delta by using the vertical derivative and Euler deconvolution for the gravity anomaly data, Vietnam. Journal of Geology, Series A, 287(3–4), 39–52. Werner S., 1955. Interpretation of magnetic anomalies of sheet-like bodies, Sveriges Geologiska Undersokning, Series C, Arsbok, 43, 6. Xu S.Z., 2006. The integral-iteration method for continuation of potential ﬁelds, Chinese journal of geophysics (in Chinese), 49(4), 1176–1182. Zhang C., Huang D.N., Zhang K., Pu Y.T., Yu P., 2016. Magnetic interface forward and inversion method based on Padé approximation, Applied Geophysics, 13(4), 712–720. CCOP, 1996. Magnetic anomaly map of East Asia, scale 1:4.000.000, Geological survey of Japan and Committee for co-ordination of joint prospecting for mineral resources in asian offshore areas.